Google Docs Utilization in Collaborative Academic Text Writing: Student Perceptions of Ease of Use, Barriers, and Continuity of Use - Mariyadi; Amriani Amir (Universitas Pendidikan Ganesha, 2026)
Technological developments have brought about online based collaborative learning through Google Docs, which needs to be analyzed and evaluated regarding the effectiveness of its use in academic text writing. This study aims to analyze, evaluate, and explore students’ interpretations of the use of Google Docs in collaborative writing activities using a qualitative approach and a phenomenological perspective. Data were collected from 13 students through semi structured interviews and then analyzed thematically to construct meanings from their experiences of using the technology. The analysis resulted in four main themes of students’ perceptions of Google Docs. The first, Perceived Ease of Use, includes ease of use, free access, and flexibility. The second, Perceived Usefulness, covers collaborative writing support, learning to write, editing, and accelerating the writing process. The third, Perceived Barriers, includes unfamiliar group members, low responsiveness among members, and limitations when using smartphones. The fourth, Perceived Continuance, involves use for collaboration, independent writing, and recommendations to others.Overall, the conclusion shows that Google Docs functions not only as a collaborative writing tool but also shapes students’ working patterns in academic writing in higher education. It encourages more structured task division, direct interaction during text development, and more active and purposeful use of technology in writing activities. In conclusion, Google Docs is considered effective for collaborative academic writing, although improvements are still needed in users’ digital literacy and technical skills. The findings imply that collaborative technology can support more interactive writing learning and provide a basis for developing systematic training and teaching strategies in higher education.